2011
DOI: 10.1039/c1cp21861a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescent sensitized fluorescent solid-state near-infrared light-emitting electrochemical cells

Abstract: We report phosphorescent sensitized fluorescent near-infrared (NIR) light-emitting electrochemical cells (LECs) utilizing a phosphorescent cationic transition metal complex [Ir(ppy)(2)(dasb)](+)(PF(6)(-)) (where ppy is 2-phenylpyridine and dasb is 4,5-diaza-9,9'-spirobifluorene) as the host and two fluorescent ionic NIR emitting dyes 3,3'-diethyl-2,2'-oxathiacarbocyanine iodide (DOTCI) and 3,3'-diethylthiatricarbocyanine iodide (DTTCI) as the guests. Photoluminescence measurements show that the host-guest film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 38 publications
4
52
0
1
Order By: Relevance
“…Recently, Ho et al reported a more efficient NIR iTMCbased LEC reaching EQEs of 1.2 %, [196] that used the orangeemitting Ir-iTMC 36 ( Figure 27) as host and different fluorescent ionic NIR laser dyes as guest. Maximum EQE values (power efficiencies) of 0.8 % (5.6 mW W À1 ) and 1.2 % (7.8 mW W À1 ) were measured, respectively.…”
Section: Light-emitting Electrochemical Cellsmentioning
confidence: 99%
“…Recently, Ho et al reported a more efficient NIR iTMCbased LEC reaching EQEs of 1.2 %, [196] that used the orangeemitting Ir-iTMC 36 ( Figure 27) as host and different fluorescent ionic NIR laser dyes as guest. Maximum EQE values (power efficiencies) of 0.8 % (5.6 mW W À1 ) and 1.2 % (7.8 mW W À1 ) were measured, respectively.…”
Section: Light-emitting Electrochemical Cellsmentioning
confidence: 99%
“…Ho et al beschrieben jüngst effizientere NIR-iTMC-LECs mit dem orange emittierenden Ir-iTMC 36 (Abbildung 27) als Wirt und verschiedenen ionischen NIRLaser-Fluoreszenzfarbstoffen als Gästen. [196] Maximale EQEWerte (und Leistungseffizienzen) von 0.8 % (5.6 mW W À1 ) und 1.2 % (7.8 mW W À1 ) wurden gemessen.…”
Section: Nahinfrarot-lecsunclassified
“…In addition, there have been numerous studies regarding the spatial distributions of the ions, charges, and dynamic p-n junctions in dynamic doping. [11][15] However, few studies have investigated responses to input frequency or timing during the dynamic doping process, and understanding such responses is imperative for simulating bio-learning processes. Comprehensive investigations are necessary to understand ion migration kinetics at the polymer/electrolyte interface under periodic electric fields.…”
Section: Introductionmentioning
confidence: 99%